Social Constellation of Warjabakti Village: A Sociological Study on Structure, Interaction, and Social Change - Gunawan, Wahyu; Amanatin, Elsa Lutmilarita; Lukman, Fahmy; Yunita, Desi (Journal of Cultural Analysis and Social Change, 2025)
This study examines how the community of Warjabakti Village in West Java, Indonesia, constructs social resilience amid structural transformation and digitalization. Employing a qualitative approach through three months of participant observation, twenty in-depth interviews, and document analysis, the research reveals that digital platforms such as WhatsApp and Facebook have redefined traditional social spaces without displacing communal values. The findings show three interrelated strategies of resilience: conserving local values, selectively adopting technology, and rearticulating social roles through hybrid gatherings and youth-led initiatives. While digitalization enhances communication efficiency and youth participation, it also generates symbolic inequalities that marginalize elders and less-connected residents. Social capital remains a key resource, bonding ties sustain trust, while bridging ties link generations, migrants, and new digital actors. Theoretically, the study contributes to global debates in rural sociology and social resilience by demonstrating how peripheral communities transform from mechanical to hybrid forms of solidarity that blend tradition with innovation. Practically, it highlights the need for inclusive village development policies that integrate social structures, technological adaptation, and participatory governance. Warjabakti exemplifies a communicative and reflective model of rural transformation in the digital era.